Pengaruh Pemberian Massage Effleurage Dengan Minyak Aromaterapi Terhadap Kualitas Tidur Malam Ibu Hamil Trimester II dan III - Theresia Salmabela Patria; Nella Vallen I.P; Resa Nirmala Jona (Lembaga Pengembangan Kinerja Dosen, 2024)
Background: Many pregnant women experience sleep disorders in the second and third trimesters, which can lead to poor sleep quality. This study aimed to determine the effect of effleurage massage with aromatherapy oil on improving the quality of nighttime sleep for pregnant women in the second and third trimesters at Anugrah Clinic. This type of research is a quasi-experiment with a control group pretest-post-test design. The population was all second- and third-trimester pregnant women at Anugrah Clinic, with as many as 46 pregnant women. The sampling technique was total sampling, with 23 pregnant women in the experimental group and 23 in the control group. The data collection tool used the Pittsburgh Sleep Quality Index (PSQI) questionnaire. Data analysis used the McNemar test. The experimental group study showed an effect of effleurage massage with aromatherapy oil on the quality of night sleep for pregnant women in the second and third trimesters, with a value of p = 0.001. The control group study showed an effect of massage effleurage on the quality of night sleep for pregnant women in the second and third trimesters, with a value of p = 0.016. Analysis of the chi-square test data to see the difference between the experimental and control groups yielded a p-value of 0.049, meaning that there was a significant difference in the post-test sleep quality of the experimental and control groups. In conclusion, the increase in sleep quality for pregnant women was more common in the experimental group; the quality of sleep for pregnant women increased to 87%, while in the control group, the quality of sleep for pregnant women increased only 56.5%. The suggestion is that it is hoped that pregnant women and health workers, in overcoming sleep disturbances in the second and third trimesters of pregnant women, can apply effleurage massage interventions with aromatherapy oils.